Aspectos psicossociais do auto-exame: implicações num outro olhar da prevenção do câncer de mama - Ellery, Ana Ecilda Lima (2004)
The breast cancer is a pathology that has crescent incidence, in the countries of higher degree of development like in the countries in development. There are evidences that its causes seem to have relation to modern life style, of difficult control. In this context, the efforts are direct to secondary prevention, in order to make an early diagnosis of tumors, trying to avoid a great number of mutilations and ensure higher survival and a better quality of life for women with this type of neoplasy. Among of the methods of precocious detection that had been recommended by Cancer National Institute, until the launch of Consensus to the Control of Breast Cancer, in April 2004, the breast self-examinations had prominence of place, beside medical exam and mammography. However, researches show the women are difficult of breast self- examination adhesion, although this is a painless, fast and free technique. The aim of this study was the comprehension of the psicossociais aspects involved in breast self-examination, in order to offer subsidy to prevention practices in breast of cancer. To realization this study, we based on the Qualitative Epistemology, Gonzalez Rey (2002). It is based on Dialectic Method and shows that the quality and quantity of facts are inseparable and interpedent. In this direction, our study pondered either the structure reality through the numbers as the qualitatives aspects. We accomplished a transversal study, of population base, with 561 women in the Sobral city, state of Ceará, Brazil. 13 women were interviewed. They were considered key – informers for survey. It was made still a group meeting with women who had the breast cancer. The process of the construction of information allowed the identification of six themes: 1. knowledge and frequency of breast self-examination and variable correlated; 2. Imputed meaning and produced sense about breast self-examination; 3. Motivation of the practice breast self-examination; 4. Resistance to practice of the breast self-examination; 5. Talks and insight sense in the education actions; 6. Re-think the preventive practices in breast cancer. Based on the process of information construction, we understand the cancer social representation, which influences the acceptation of breast self-examination. The breast self-examination is associated with breast cancer and this fact increases the fear of women. We conclude that the breast self-examination isn’t a simple technique to make. It needs support to find any alteration in breast. We also conclude that there is sufficient knowledge to make primary prevention in breast cancer. It is necessary to understand that the illness process is complex and involves subjective, physics, social and environmental aspects.